2014
DOI: 10.1371/journal.pone.0093458
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Nrf1 Is Topologically Repartitioned across Membranes to Enable Target Gene Transactivation through Its Acidic Glucose-Responsive Domains

Abstract: The membrane-bound Nrf1 transcription factor regulates critical homeostatic and developmental genes. The conserved N-terminal homology box 1 (NHB1) sequence in Nrf1 targets the cap‘n’collar (CNC) basic basic-region leucine zipper (bZIP) factor to the endoplasmic reticulum (ER), but it is unknown how its activity is controlled topologically within membranes. Herein, we report a hitherto unknown mechanism by which the transactivation activity of Nrf1 is controlled through its membrane-topology. Thus after Nrf1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
145
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(162 citation statements)
references
References 3 publications
17
145
0
Order By: Relevance
“…1B, middle panel ). It should be herein noted that distinct TCF11/hNrf1 isoforms were separated in the pH 8.9 Laemmli SDS–PAGE containing 8% polyacrylamide, and therefore their electrophoretic mobility on the pH 8.9 SDS–PAGE gel is obviously different from the equivalent mobility exhibited on the pH 7.0 NuPAGE containing 4–12% polyacrylamide [36–38]).…”
Section: Resultsmentioning
confidence: 96%
“…1B, middle panel ). It should be herein noted that distinct TCF11/hNrf1 isoforms were separated in the pH 8.9 Laemmli SDS–PAGE containing 8% polyacrylamide, and therefore their electrophoretic mobility on the pH 8.9 SDS–PAGE gel is obviously different from the equivalent mobility exhibited on the pH 7.0 NuPAGE containing 4–12% polyacrylamide [36–38]).…”
Section: Resultsmentioning
confidence: 96%
“…Nrf1 is attached to the ER membrane via its NH 2 -terminally localized N-terminal domain (NTD) (Wang and Chan, 2006; Zhang et al, 2006). As opposed to other membrane-tethered transcription factors such as SREBP or ATF6 the activation of Nrf1 does not appear to involve signal regulated intramembrane proteolysis, but rather a change in its posttranslational glycosylation status (Zhang et al, 2007; Zhang et al, 2014b). It has been suggested that deglycolsylation of Nrf1 changes the topology and the biochemical function of transcription activation domains ultimately resulting in target gene activation (Zhang et al, 2014b).…”
Section: Relationship Of Cnc With Nrf2 and Nrf1mentioning
confidence: 96%
“…Indeed, Nrf1, like its more intensely studied cousin Nrf2, controls the transcription of a battery of antioxidant and stress defense genes. Nrf1 activity increases in response to oxidative stress and glucose depletion (Chen et al, 2003; Ohtsuji et al, 2008; Zhang et al, 2014b). In addition, signaling through the TorC1 complex can stimulate the expression of proteasome subunit genes by a mechanism that relies on Nrf1 but is Nrf2 independent (Zhang et al, 2014a; Zhang et al, 2014b).…”
Section: Relationship Of Cnc With Nrf2 and Nrf1mentioning
confidence: 99%
See 2 more Smart Citations